Photography as a process: the experience in a photography workshop with young people from Badalona (Barcelona, Spain) - Holgado, Claudia (2018)
Within the framework of the Secondary School Accompaniment Program of the Social Space of Llefi à, Badalona (Barcelona, Spain), I carried out a photography workshop whose main objective was to allow young people to experiment with the photographic image and build personal visual narratives. This proyect proposes to understand the photographic experience as a process and not only as an aesthetic result. The article aims to account for the methodology used in the collaborative construction of a workshop and, this way, narrate the dynamics, encounters and links that can be generated from the photographic learning and the resulting images.